Antibacterial and antibiofilm activities of tribulus terrestris methanolic extract against Streptococcus mutans, Streptococcus sobrinus, and Lactobacillus acidophilus: An in vitro study - Ali Azarm; Fatemeh Ayoobi; Mohammad Zare-Bidaki; Mohammad Taheri; Ebrahim Rezazadeh Zarandi (Dental Research Journal)
Background Tribulus terrestris (TT) extract has shown good antibacterial activity against some bacteria. However, there are limited data on its cariogenic properties. This in vitro study aimed to evaluate the antibacterial and antibiofilm activities of TT extract against Streptococcus mutans (S. mutans), Streptococcus sobrinus (S. sorbinus), and Lactobacillus acidophilus (L. acidophilus) as the important cariogenic bacteria. Materials and Methods This study was designed in an experimental model (in vitro). Phytochemical tests were carried out to detect herbal compounds in the TT extract. Agar well diffusion was performed to compare the extract (500–62.5 mg/mL) with different concentrations of chlorhexidine (2–0.25 mg/mL). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the TT extract and chlorhexidine were also determined. The lowest concentration showing ≥50% inhibition of biofilm formation (MBIC50) was determined using crystal violet assay. Further, the time-kill assay (Log of CFU/mL) was performed, and acid production (pH) was measured at 1 × MIC concentration in 2, 4, 8, 12, and 24 h. Data analysis conducted using SPSS software (v26, IBM) involved One-way analysis of variance, Tukey post hoc tests, and t-test to compare concentrations and groups. Significance level is set at 0.05. Results The TT extract mostly consisted of flavonoids. Its inhibition zones in the well diffusion test were statistically comparable with chlorhexidine in some concentrations (P > 0.05). The MIC of the TT extract was 15.625 mg/mL for all tested bacteria, whereas the MBC ranged from 31.25 to 62.5 mg/mL. Further, the MBIC50 ranged from 7.8125 to 15.625 mg/mL for the extract. Time-kill assay showed that the bactericidal activity of the TT extract lasted for 8, 12, and 2 h for S. mutans, S. sobrinus, and L. acidophilus, respectively. The acid production decreased obviously after 8 h. Conclusion The TT extract showed good time-dependent antibacterial and antibiofilm activity, as well as acid production inhibition, against cariogenic bacteria in laboratory experiments.